Australian household adoption of solar photovoltaics: A comparative study of hardship and non-hardship customers. (January 2022) - Dodd, Tracey; Nelson, Tim
Abstract: Prior studies establish that electricity systems across the globe need to transition toward renewable energy and that renters have a low adoption of effective means to do so through access to household solar photovoltaics (PV). Yet, the economic, environmental, and social costs of low PV adoption by people who have trouble paying their electricity bills (hardship customers), who are more likely to be low-income tenants, remain understudied. Drawing on electricity use data from an Australian energy retailer we compare the performance of PV for hardship customers against 'average' households. Results illustrate that if society could achieve greater solar PV installation on hardship homes, annual grid-based electricity consumption could be reduced by 40%, lowering greenhouse gas emissions by 1.6 tCO2 e per household annually and energy bills by 2908 per low-income household over 15 years. We illustrate how Australian policy could be re-oriented to encourage greater PV adoption on hardship properties, including through support for a new market structure that distributes the economic benefits of PV between renters and landlords. Highlights: A novel dataset examining Electricity Hardship Customers (EHC) energy usage is analyzed. Data show EHC use more electricity than standard customers. PV deployment on EHC homes reduces grid-based electricity consumption by up to 40% per household. This could lower greenhouse gas emissions by 1.6 tCO2 e per EHC household. To achieve this, new market mechanisms are required, with a NFP option presented.